KELIMPAHAN IKAN CHAETODONTIDAEDAN POMACENTRIDAE PADA EKOSISTEM TERUMBU KARANG DI PERAIRAN BEDUKANG KABUPATEN BANGKA - Fatimah Fatimah; Kurniawan Kurniawan; Indra Ambalika Syari (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2018)
Bedukang waters areas have high natural resources and environmental services, including coral reefs ecosystem. The aim of this study to analyze the abundance of Chaetodontidae and Pomacentridae.Percentage of live coral cover, and relationship of Chaetodontidae and Pomacentridae with habitat conditions. This research was conducted in March 2018. Belt Transect method used to collect fishes data and Line Intercept Transect to coral reefs. Data analysis uses Principal Component Analysis (PCA) and Correspondent Analysis (CA). The results showed 14 fishes species, 2 species of fishes family Chaetdontidae, and 12 species of fishesPomacentridae 2.267 ind/ha. The highest species composition is Neoglyphidodon nigroris and the lowest Amphiprion clarkii. The abundance of Chaetodontidae and Pomacentridae 14 species. The highest abundance at station 4 was 4,860 ind/ha and the lowest at station 1 was 820 ind/ha. The percentage of coral reef cover is in poor, medium and good condition with an average of 39.66%. The abundance of Chaetodontidae and Pomacentridae fish in Bedukang waters is influence by the percentage of live coral and algae cover. Chaetodontidae and Pomacentridae in Bedukang waters favor Acropora, Euphylia, Favites, Fungia, Galaxia, Goniopora, Lobophyllia, Pavona, Porites, Psammocora,Turbinaria, Cypastrea, Montipora, Platygyra andSymphylliagenus